Job Satisfaction’s Impact on Employee Performance: The Mediating Role of Employee Engagement - Maryati, Tri; Danupranata, Gita; Musoli, Musoli; Nugraha, Syahdani Satria (SENTRALISASI, 2024)
This study aims to examine the impact of job satisfaction (JS) on employee performance (EP) and examine the role of employee engagement (EE) in their relationship. This study was undertaken based on settled theories of job satisfaction (JS), employee performance (EP), and employee engagement (EE). It maintains that the employee's perceived JS can boost EP and that EE serves as a mediator in this relationship. Using a deductive approach and a quantitative research design, the study investigated the correlation between JS and EP in PKU Muhammadiyah Yogyakarta Hospital. Data from 131 respondents were analyzed utilizing AMOS with the help of SEM software. The data analysis uncovered that employee job satisfaction (JS) positively impacted performance (EP) in PKU Muhammadiyah Yogyakarta Hospital. In addition, employee engagement (EE) acted as a mediator between JS and EP. Job satisfaction felt by employees and creating employee engagement could boost EP in PKU Muhammadiyah Yogyakarta Hospital. The study highlights that providing job satisfaction to employees has broad benefits, including greater employee engagement, enhanced employee work, and a positive contribution to the development of PKU Muhammadiyah Yogyakarta Hospital. Practically, this research highlights the importance of creating employee job satisfaction. Employee satisfaction is something that organizations must pay attention to because it affects employee engagement and employee performance. Employees will be more active in carrying out their assigned tasks if they feel satisfied. Employees who feel connected (engaged) with the company will have an awareness of the organization so that employees will provide their best abilities and skills for the success of the organization. The theoretical implications of testing the correlation between job satisfaction and employee engagement on employee performance can enrich existing behavioral theories in organizations.